Mother ocean father nation : a novel - Batsha, Nishant (Ecco, an imprint of HarperCollinsPublishers, 2022)
"A riveting, tender debut novel, following a brother and sister whose paths diverge--one forced to leave, one left behind--in the wake of a nationalist coup in the South Pacific"--